A new supramolecular catalytic system: the self-assembly of Rh8 cage host anthracene molecules for [4 + 4] cycloaddition induced by UV irradiation. Issue 28 (2nd July 2020) - Yu, Wei-Bin; Qiu, Feng-Yi; Sun, Po; Shi, Hua-Tian; Xin, Zhi-Feng
Abstract : The supramolecular assembly is significant in host–guest chemistry. In this work, a new supramolecular system assembled through a distorted cuboid was introduced. Moreover, the [4 + 4] cycloaddition reaction of the guest molecules was further studied under UV light. Abstract : The supramolecular assembly, used as a molecular reactor, is of great significance in host–guest chemistry. In this work, we used a tetratopic pyridyl ligand as a building block to hierarchically combine a slightly twisted cuboid with half-sandwich rhodium fragments. The cuboid directionally self-assembled hydrophobic pockets that can encapsulate conjugated molecules like anthracene (ANT) as guests in solutions, by supramolecular interactions including hydrogen bonding and hydrophobic interactions. The array of the ANT molecules in the confined pockets was subjected to a [4 + 4] photocycloaddition reaction under UV light irradiation as an external stimulus in a methanol solution. Furthermore, the mechanism underlying the process was proposed. The cuboid was fully characterized by 1 H NMR, single-crystal X-ray diffraction (SCXRD), and mass spectrometry (MS), and its host–guest and cycloaddition processes were monitored by 1 H NMR spectroscopy and UV-visible spectrophotometry.